COMPREHENSIVE CONTROL OF PHYSICAL AND COMBAT TRAINING OF CADETS - Burxonov Bahodir Hayotovich (Proximus Journal Publishing, 2024)
The main purpose of physical and combat training of cadets in educational institutions of the Ministry of Internal Affairs of the Republic of Uzbekistan is to educate harmoniously developed specialists for internal affairs bodies capable of effectively solving operational and service tasks, including in extreme conditions.
Keywords: physical training; dynamics; obstacle course; combat training